Cubic spline interpolation analysis using maple package - Qani, yalda (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2023)
We talk about using the Maple package for abstract cubic interpolation analysis. We review the capabilities of the package and provide an in-depth analysis of cubic spline interpolation. Our analysis shows the effectiveness of this method in solving complex problems in different fields. In this analysis, we will examine the basics of cubic spline interpolation, including how it works, its advantages and disadvantages, and how to implement it using the Maple software package. We will also discuss some real-world applications of cubic spline interpolation, such as data smoothing and curve fitting. Through this analysis, we hope to provide a comprehensive understanding of cubic spline interpolation and its importance in various contexts. Using Maple, cubic splines can be easily calculated, plotted, and even manipulated to suit specific needs. In addition, Maple allows the creation of interactive graphs, which can be used to explore the properties of cubic lines and gain a deeper understanding of their behavior.